Light-induced effects against Candida albicans and Staphylococcus aureus (Research, Society and Development, 2022)
Objectives: The present study evaluated the action of LED light sources at different wavelengths on cell viability, lipid peroxidation, and Top I and II gene expression of Candida albicans and Staphylococcus aureus. Methods: Planktonic cultures were subjected of illumination, and the post- irradiation cell proliferation was assessed by quantification of metabolic mitochondrial activity. Next, the response of the microorganisms to the treatments was assessed. Results: Cell viability (CFU/mL) reduction occurred only for the fungus by 0.5 and 0.6 log10 using yellow LED 0.1 and 10 J/cm2, respectively. For S. aureus, none of the evaluated wavelengths reduced cell viability versus the control. Production of intracellular ROS occurred in all tested light doses and wavelengths, except for 0.1 J/cm2 of yellow LED for both microorganisms. Lipid peroxidation occurred only for C. albicans after exposure to 10 J/cm2 of yellow LED, 15 and 50 J/cm2 of blue LED, and 300 and 500 lux of white LED. The two doses of blue light and red light decreased the expression of TOP II of C. albicans and TOP I of S. aureus. The two doses of yellow and white lights promoted an increase in the expression of the genes that encode TOP II and TOP I for both species. Conclusion: The results demonstrated that the mechanisms of action of white LEDs and at blue (455 nm), red (660 nm) and yellow (590 nm) wavelengths seem to be related to the production of ROS, lipid peroxidation, and DNA damage.